ANALYSIS OF LABORATORY MANAGEMENT IMPLEMENTATION AND THE LEVEL OF ACCURACY OF THE EXAMINATION RESULTS IN HIV/AIDS COMMUNITY HEALTH CENTERS IN THE TULUNGAGUNG DISTRICT - Hariyanto Hariyanto; Indasah Indasah; Sandu Siyoto (Journal for Quality in Public Health, 2017)
The community health Centers is the first-level health facilities (FKTP), which is responsible for health community districts (Kemenkes, 2016). The dynamics of the health problems facing the community is very diverse from various aspects can be seen overall demen Bio Social Sepiritual Neorologis. The type of research used in this research is observational analysis is a method of research conducted with the observations of behaviour, to create a picture of a State specific populations that are systematic and accurate. Observational research is research that explores how and why the quality management is correlated against the results, then do the analisia dynamics of the correlation between the factors that affect the accuracy of those results. In this study using a research korelasional that can be interpreted as a process of systematic investigation to find out the relationship between two or more variables (Sulistyaningsih). Statistics Regression test on logistics, obtained significant value of 0.00 (value p), valued at p = α = 0.05 0.00 < → HO is rejected, meaning that there is a correlation, laboratory management implementation and the level of accuracy of the inspection results HI Classification indicates the value of the overall percentage of 97.4%, which means that the accuracy of these studies amounted to 97.4%. This is because nearly all Clinics and Ngunut Campurdarat shows results as SOP by 25% (29 respondents), 18.97% of clinics Ngantru results (22 respondents). Meanwhile Clinics Simo 15.52% result (18 respondents) the results as SOP and 9.48% (11 respondents) the results is not appropriate.